SUSTAINABLE MODELS AND STRATEGIC PROSPECTS FOR SOCIAL SUPPORT OF YOUTH (Western European Journal of Historical Events and Social Science, 2025)
This article examines the sustainable models and long-term strategic prospects for social support of youth within the rapidly changing dynamics of contemporary society. The analysis highlights the interconnection between economic development, political stability, spiritual processes, and technological progress. Sustainable models are interpreted as longterm, self-renewing systems capable of integrating national values with modern technologies while ensuring youth intellectual development, cultural continuity, and spiritual resilience. Drawing on the perspectives of leading scholars, the article explores the significance of flexible educational systems, digital transformation, moral-ethical development, and national identity in shaping youth support strategies. The study concludes that multi-level governance, civil society engagement, public–private partnerships, and integration of innovative social technologies are essential to ensuring sustainable youth development and strengthening overall social stability